Dexamethasone doses in patients with COVID-19 and hypoxia: A systematic review and meta-analysis - Munch, Marie Warrer; Granholm, Anders; Maláska, Jan; Stašek, Jan; Rodriguez, Pablo O; Pitre, Tyler; Wilson, Rebecca; Savović, Jelena; Rochwerg, Bram; Svobodnik, Adam; Kratochvíl, Milan; Taboada, Manuel; et al. (Acta anaesthesiologica Scandinavica, 2024)
BACKGROUND: The optimal dose of dexamethasone for severe/critical COVID-19 is uncertain. We compared higher versus standard doses of dexamethasone in adults with COVID-19 and hypoxia. METHODS: We searched PubMed and trial registers until 23 June 2023 for randomised clinical trials comparing higher (>6 mg) versus standard doses (6 mg) of dexamethasone in adults with COVID-19 and hypoxia. The primary outcome was mortality at 1 month. Secondary outcomes were mortality closest to 90 days; days alive without life support; and the occurrence of serious adverse events/reactions (SAEs/SARs) closest to 1 month. We assessed the risk of bias using the Cochrane RoB2 tool, risk of random errors using trial sequential analysis, and certainty of evidence using Grading of Recommendations Assessment, Development and Evaluation (GRADE). RESULTS: We included eight trials (2478 participants), of which four (1293 participants) had low risk of bias. Higher doses of dexamethasone probably resulted in little to no difference in mortality at 1 month (relative risk [RR] 0.97, 95% CI: 0.79-1.19), mortality closest to Day 90 (RR 1.01, 95% CI: 0.86-1.20), and SAEs/SARs (RR 1.00, 95% CI: 0.97-1.02). Higher doses of dexamethasone probably increased the number of days alive without invasive mechanical ventilation and circulatory support but had no effect on days alive without renal replacement therapy. CONCLUSIONS: Based on low to moderate certainty evidence, higher versus standard doses of dexamethasone probably result in little to no difference in mortality, SAEs/SARs, and days alive without renal replacement therapy, but probably increase the number of days alive without invasive mechanical ventilation and circulatory support.
Keywords: Adult; COVID-19 Drug Treatment; pacienti; dospělí; Patients; COVID-19; hypoxie; Dexamethasone; Hypoxia; dexamethason; Humans; lidé; farmakoterapie COVID-19